2016
DOI: 10.5507/bp.2015.049
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year survival and prognostic markers in one thousand patients with advanced heart failure. A single-centre analysis

Abstract: Aim. Patients with advanced heart failure (HF) represent a pool of candidates for heart transplantation and long-term mechanical circulatory support devices. The aim of our study was to determine simple and reliable markers of one-year mortality for selection of the most suitable patients for heart replacement therapy. Methods and Results. One thousand consecutive patients with HF (mean age 49 ± 10.9 years; 86.8% males) referred to a single tertiary centre from January 1998 to January 2010 in order to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[10][11][12] In addition to being in a different species, other study design differences make direct comparison with this study difficult. For example, some human studies used dose at discharge from hospitalization for advanced heart failure, 13 dose prescribed at the first ambulatory visit for heart failure, 12 or baseline dose from clinic visits for advanced heart failure. 10 This association, however, could be related more to disease severity, than to the diuretic dose.…”
Section: Survival Analysismentioning
confidence: 99%
“…[10][11][12] In addition to being in a different species, other study design differences make direct comparison with this study difficult. For example, some human studies used dose at discharge from hospitalization for advanced heart failure, 13 dose prescribed at the first ambulatory visit for heart failure, 12 or baseline dose from clinic visits for advanced heart failure. 10 This association, however, could be related more to disease severity, than to the diuretic dose.…”
Section: Survival Analysismentioning
confidence: 99%
“…Following the title and abstract screening process, 292 studies were deemed eligible for full‐text screening. Ultimately, during the final phase of full‐text screening, 65 studies (comprising 88 cohorts) met the inclusion criteria and were included in the subsequent meta‐analysis 10–74 . One additional study was identified through a manual cross‐reference of the included studies, bringing the total to 66 studies 75 (online supplementary Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…During years 2010 and 1998, 1000 patients with heart failure referred by cardiologists to a single tertiary center in order to assess the indication for heart transplantation were hospitalized and monitored (86.8 % men and 13.2 % women, mean age 49.0 ± 10.9 years). The majority of patients (80.8 %) had severe left ventricular systolic dysfunction with ejection fraction < 30 %; 1.8 % of patients had preserved left ventricular ejection fraction ≥ 50 % (8). Despite of the number of CM patients and the availability of NGS methods, the current diagnostic tests in Slovakia are still based on Sanger sequencing of a few genes (9).…”
Section: Introductionmentioning
confidence: 99%